Japanese fixed income markets : money, bond and interest rate derivatives - Batten, Jonathan; Fetherston, Thomas A.; Szilagyi, Peter G., 1976- (Elsevier, 2006)
Provides an improved understanding of the Japanese Fixed Income Market.